Sexual and Reproductive Health Education in Adolescents of Nepal: Current Status, Knowledge Gaps, and Strategic Interventions - Prajapati, Rama; Sah, Anil Kumar; Koirala, Anisha; Mulmi, Asmita; Thapa, Nirjala; Khanal, Pooja; Thapa, Prakriti; Choudhary, Khirendra; Giri, Suja (Journal of Multidisciplinary Research Advancements, 2024)
Sexual and reproductive health (SRH) in Nepal faces significant challenges, including high rates of early marriage and motherhood, limited access to quality education, and low contraceptive utilization, with prevalent stigma surrounding sexually transmitted infections (STIs) and HIV/AIDS. Despite high awareness of contraceptives among adolescents, actual usage remains low, highlighting critical gaps in access and education. This review paper used a desktop research approach to examine existing literature on SRH education in Nepal. This study was conducted to identify SRH challenges and propose actionable solutions to improve outcomes for youth in Nepal. The findings reveal a pressing need to strengthen legal frameworks against child marriage, the integration of Comprehensive Sexuality Education (CSE) into school curricula, and the development of youth-friendly health services. Additionally, the study identifies the importance of community engagement and parental involvement in promoting supportive environments for young people. This research contributes to a deeper understanding of the barriers to effective SRH education and services in Nepal and offers practical recommendations for addressing these issues.